(untitled) (Medicine Today, 2020)
Introduction:Cirrhosis of liver is common Medical problem in our country and causing for significant morbility & mortality. This study was aimed to findout actiology and clinical presentation of cirrhosis in this southern part of Bangladesh. Materials & Methods: An observantional study was conducted in Khulna Medical College Hospital from January 2016 to June 2016. That included adult (>15yrs) cirrhosis patient in medicine ward on the basis of history & clinical examination. Results: Common age is (37-48)yrs, 80% were male patient. Male Female ratio 4:1. Anorexia & dyspepsia were the most common symptom. 78% presented with ascites 34% presented with variceal bledding. Aetiology are Hepatitis B (52%), Hepatitis C (24%) & idiopathic 16%. Conclusion: Screening for chronic liver disease should include history and physical examination, serum transaminase measurement, upper abdominal ultrasonography, and in some case, fibroscan. Management of patient with cirrhosis should be prevention & early intervention to stabilize disease progression and to avoid or delay clinical decompensation and the need for liver transplantation. Medicine Today 2020 Vol.32(2): 100-103